Indoor air quality and health in schools - Ferreira, Ana Maria da Conceição (2014)
Objective: To determine whether indoor air quality in schools is associated with the prevalence of allergic and respiratory diseases in children. Methods: We evaluated 1,019 students at 51 elementary schools in the city of Coimbra, Portugal. We applied a questionnaire that included questions regarding the demographic, social, and behavioral characteristics of students, as well as the presence of smoking in the family. We also evaluated the indoor air quality in the schools. Results: In the indoor air of the schools evaluated, we identified mean concentrations of carbon dioxide (CO2) above the maximum reference value, especially during the fall and winter. The CO2 concentration was sometimes as high as 1,942 ppm, implying a considerable health risk for the children. The most prevalent symptoms and respiratory diseases identified in the children were sneezing, rales, wheezing, rhinitis, and asthma. Other signs and symptoms, such as poor concentration, cough, headache, and irritation of mucous membranes, were identified. Lack of concentration was associated with CO2 concentrations above the maximum recommended level in indoor air (p = 0.002). There were no other significant associations. Conclusions: Most of the schools evaluated presented with reasonable air quality and thermal comfort. However, the concentrations of various pollutants, especially CO2, suggest the need for corrective interventions, such as reducing air pollutant sources and improving ventilation. There was a statistically significant association between lack of concentration in the children and exposure to high levels of CO2. The overall low level of pollution in the city of Coimbra might explain the lack of other significant associations.